Tatak pilipino [episode 59]. ([Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
Chinese in the Philippines (5 min.) -- Astrologers ( 5 min.) -- Chinese mestizo (5 min.) -- Aphrodisiacs (5 min.) -- Chinese businessmen (2 min.) -- Chinese self defense (5 min.) -- Chinese sport-Wushu (5 min.) -- Ang Kiukok (5 min.) -- Chinatown (5 min.) -- Batangas no Chinese policy (5 min.)
In English and Pilipino.
Keywords: Aprodisiacs; Chinese -- Philippines; Sports -- China; Soyfoods -- Philippines; Astrologers; Chinatown (Manila).; Ma Mon Luk